Risk management in health care centres - Cichońska, Dominika; Iltchev, Petre (Polish Journal of Public Health, 2011)
Introduction. Risk is omnipresent in human life and in all its areas. Levels of risk increase along with civilization development; however, its acceptability increases as well. There are areas, for instance, medicine, where identification of risk is expected to greater extent as well as detecting its source and then systemizing, monitoring and decreasing it to acceptable levels. Aim. The aim of this paper is to present methods of risk management and their applicability in health care system in Poland. Material and method. The research covered 70 hospitals as a representative group of Polish public hospitals of directed survey with the hospitals management and of completing the questionnaire concerning risk management. The research was carried out by the group of researchers from the Medical University of Lodz in the years 2006-2007. Discussion. The discussion covers risk management systems for public health care centers (their advantages and disadvantages). Within the case study one of the risk management programs obtained in the examination in one of district hospitals has been described. Conclusions. It is advisable to create the instructions which would formalize the rules of risk management in health care centers using already used by for-profit enterprises risk management techniques such as: methods of event trees and fault trees (damage, unfitness), VaR or Balanced Scorecard. Therefore, it is particularly important to create a risk management programme, the execution of which guarantees safety in health care units.